INDUKSI KETAHANAN KLON KARET TERHADAP PENYAKIT GUGUR DAUN (Colletotrichum gloeosporioides) DENGAN PEMBERIAN ASAM SALISILAT - Radite Tistama; Cici Indriani Dalimunthe (Institut Teknologi Sawit Indonesia, 2018)
Preliminary trail using food poisoning technique obtained output that 0,2 g/L salicylic acid (SA) inhibited growth of leaf fall disease of rubber tree such as Colletotrichum gloeosporioides, Oidium heveae as well as Corynespora cassiicola.The SA inhibited growth of the third leaf fall desease more than 85% in in vitro. The next observation aimed to knowing the eﬀect of SA in growth inhibitionof leaf desease onrubber tree in polybeg. Three level of SA concentration were spraied to the rubber tree young leaf after wo days inoculated with C. gloeosporioides spores. The optimal concentration was used for observation the response of rubber clones PB 260, IRR 122 and IRR 104 to C. gleiosporoides before and after SA spraying. The SA 0,5 g/L decreased the infection intensity of C. gloeosporioides via inducing of the systemic aquired resistance(SAR).There were variation of the infection intensity in the SA treated rubber clones to C. gloeosporioides between 10% to 18%.